Proyecto de prefactibilidad para la creación de una empresa productora de miel de abeja sin aguijón (meliponas) en la parroquia de vicentino del cantón Puyango y su comercialización será en la ciudad de Loja - Armijos Lima, Jose Luis (2022)
The general objective of this is to elaborate a "PRE-FEASIBILITY PROJECT FOR THE CREATION OF A STINGLESS BEE HONEY PRODUCING COMPANY (MELIPONAS) IN THE VICENTINO PARISH OF THE CANTON PUYANGO AND ITS COMMERCIALIZATION WILL BE CIUDAD DE LOJA", for which the market, technical, administrative legal, economic and financial evaluation studies were carried out. The deductive, inductive and statistical methods were used, as well as information collection techniques such as the survey and the interview; the chosen market segment was 56,761 families from the urban sector of the city of Loja. The market study determined the unsatisfied demand for catana honey, which is 64,509,545 milliliters of catana honey, representing 258,038 bottles of 250 milliliters. In the technical study it was determined that 8,640 bottles of honey of 250 milliliters will be produced, which represents 90% of the capacity used, obtaining a market share of 3.35%; the company will be located in the parish of Vicentino, Puyango canton, province of Loja. “MELINATIVA Cía. Ltda” will start its activities with two people. The required investment is $51,865.41 dollars, of which the partners will contribute $29,865.41 and the $22,000.00 will be financed by BanEcuador at an interest rate of 11.25%. With the financial evaluation, the following was obtained: (VAN) which is $21,183.92, a positive value, (IRR) is 24.78%, which is greater than the opportunity rate, (RBC) is $0.80 cents per each dollar invested, (TRC) is 3 years 0 months and 29 days, in addition the project is not sensitive with an increase in costs of 32% and a decrease in income of 20%. Obtaining as a final result that its execution is feasible